Whether in the body or out of the body? - Dwyer, Mary E (Spunti e Ricerche, 2016)
Dante’s bodily state in his journey to the Other World has already placed him in an exclusive class in relation to medieval Vision Literature since only one of those travellers made the journey in that state, and in earlier classical and Biblical/accounts it was also very rare. The poem’s claim to an experience of the Beatific Vision while the soul was joined to the body, would place him in an even more exclusive category. Hence the insistence on this theme throughout the work. At the end of the Paradiso however, it could perhaps be said that in that final ecstatic experience, Dante was, like St Aquinas’ St Paul, both in the body, physically, and, in his "abstracted state" also out of it.